THE INTRODUCTION OF SCIENCE CONCEPT FOR EARLY CHILHOOD - asiyah Asiyah; abdul Aziz mustamin (Al Fitrah: Journal Of Early Childhood Islamic Education, 2019)
The purpose of this study is to conceptually describe learning to introduce the concept of science to children and to analyze the development of children's abilities in knowing science. This type of research is library research. The results of this study include: (1) the implementation of learning to introduce the concept of science to children which is done through learning with simple science experiments in accordance with the characteristics of children and school conditions (2) the child's ability to recognize science. Keywords: Concepts, Learning, Science, Children